PENGUATAN KECERDASAN EMOSIONAL SISWA SEKOLAH DASAR MELALUI LAYANAN BIMBINGAN DAN KONSELING BERBASIS KELAS - Agus Susilo, Candres Abadi, (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
Emotional intelligence is an important aspect in the development of elementary school children that plays a major role in shaping character, social skills, and readiness to learn. However, the reality in the field shows that many students still have difficulty recognizing, managing, and expressing their emotions appropriately. This study aims to describe the effectiveness of classroom-based guidance and counseling services in enhancing emotional intelligence among elementary school students. The research method used is a qualitative descriptive study with a case study approach. The research subjects were fifth-grade students at a public elementary school in Lubuklinggau City who exhibited diverse emotional dynamics. Data collection techniques included observation, interviews, and documentation. The results of the study indicate that integrating counseling services into classroom activities through a participatory, reflective, and communicative approach can enhance students' understanding of their own emotions and those of others, conflict management skills, and empathy toward peers. Classroom teachers, who act as facilitators and initial counselors, play a key role in creating a supportive learning environment for students' emotional development. These findings emphasize the importance of synergy between elementary education and counseling science in supporting children's holistic growth. The implications of this study point to the need to strengthen elementary school teachers' competencies in basic classroom-based counseling services to support the achievement of the Pancasila learner profile.